Multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capability as well as preparation method and application of multifunctional biomimetic mineralized hydrogel

By blending negatively charged degradable polymer compounds, small phosphate-containing molecules, metal ions and bioactive factors and preparing bioactive hydrogels through in-situ mineralization and crosslinking, the existing bone repair materials have been solved, and the multi-factor sequential release of materials and efficient bone tissue repair are achieved.

CN119680010APending Publication Date: 2025-03-25CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510062843.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing bone repair materials have low biological activity and cannot release biologically active factors in sequence as needed. The preparation method is complex and is not suitable for clinical transformation.

Method used

Bionic mineralized hydrogels with multi-factor sequential release capabilities were prepared by blending negatively charged polymer compounds, phosphate-containing small molecules, metal ions and bioactive factors.

Benefits of technology

The multi-factor sequential release of materials is achieved, biocompatibility and biodegradability are improved, bioactive factors can be released as needed, bone tissue repair is promoted, and the preparation process is simplified, which is suitable for clinical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of medical high polymer materials, in particular to multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capacity as well as a preparation method and application of the multifunctional biomimetic mineralized hydrogel. The biomimetic mineralized hydrogel provided by the invention can automatically adapt to and fill irregular bone wounds, and the mechanical property of the hydrogel is remarkably improved by prolonging the environment temperature of a human body or the mineralization time. Functional phosphate radical-containing small molecules loaded in the hydrogel are combined with metal ions to form compact crystals, so that long-term and effective release can be realized. The physical interaction strength of the metal ions and the bioactive factors loaded in the gel in the mineralized gel is different, so that the difference of the release speed is realized. The biomimetic mineralized hydrogel provided by the invention can also be converted into biomimetic phosphate hydrogel in the later stage of bone repair to further promote the repair of bone wound positions, which shows that the biomimetic mineralized hydrogel has good biocompatibility and biodegradability, low hemolysis rate and cytotoxicity, and can effectively promote bone tissue repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical polymer materials, in particular to a multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capability and a preparation method and application thereof. Background Art

[0002] As a dynamic load-bearing tissue, bone tissue has many important physiological functions in the human body, such as maintaining body shape, detoxification, and protecting bone marrow or organs. At present, the main participants in my country's bone repair material industry include foreign companies such as Johnson & Johnson, Stryker, and Medtronic, as well as local companies such as Zhenghai Bio, Aojing Medical, Sanyou Medical, and Sanboma Bio, showing a rapid development of local companies as a whole. According to statistics, there are currently more than 400 bone fillers approved by the FDA. The market seems to be saturated, but in fact, there are only a handful of products that truly meet clinical needs. Therefore, the study of new high-activity, efficient bone repair materials that release active biological factors in order on demand and have simple preparation processes can not only alleviate clinical needs, but also help solve the technology in the field of bone repair, which has a significant role in my country's social and economic development.

[0003] At present, most of the existing bone repair materials do not take into account the composition and structure of natural bone tissue in their design, have low bioactivity, and cannot achieve the on-demand sequential release and adaptive integration of bioactive factors, especially for some severe defects and irregular wound shapes. They cannot be fully filled, degrade quickly, and the degradation products are toxic, which affects bone repair. Bioceramics are a type of inorganic biomaterial with good osteoconductivity and osteoinductivity. They play an important role in bone tissue engineering, but their brittleness limits their application in bone tissue engineering. In addition, natural polymers and synthetic polymers are commonly used in bone tissue engineering. However, natural polymers have low mechanical strength and usually need to be modified. Compared with natural polymers, synthetic polymers provide more possibilities for chemical and molecular modification, which is convenient for adjusting system performance according to specific application requirements. However, both bioceramics and polymers are only single components of bone composition, and their properties are relatively simple. Subsequently, in order to further simulate the structure and composition of human bones, organic-inorganic composites emerged; this synthetic composite material combining organic and inorganic components provides a unique, powerful and versatile material for bone tissue engineering. It is worth noting that, inspired by the biomineralization process in nature, mineralized hydrogels are prepared by in situ mineralization of inorganic minerals in hydrogel matrices. They are one of the typical representatives of organic-inorganic composite materials, achieving a high degree of biomimetic in terms of structure and composition. However, mineralized hydrogels still have the disadvantages of low bioactivity, inability to release on demand, and inability to integrate adaptively.

[0004] Therefore, how to effectively combine the three characteristics of bioactivity, sequential release on demand, and adaptive integration so that a material can meet the requirements of material performance at different stages of bone repair: in the early stage, it can completely fill wounds of any shape and solidify within a certain period of time to meet the requirements of material performance for bone repair; during the entire treatment period, bioactive factors can be released sequentially on demand at different stages to efficiently promote the repair of bone defects; in the later stage of treatment, bone repair materials also need to have a degradation rate that matches the rate of bone regeneration. This has become one of the urgent problems to be solved in the field of bone repair materials, and it plays a very important role in promoting the clinical transformation of mineralized hydrogel bone repair materials.

[0005] In addition, most of the current biomimetic mineralized hydrogels are prepared by directly immersing chemically cross-linked scaffolds into supersaturated metal ion solutions. In this case, ions diffuse freely into the hydrogel to form minerals randomly distributed within the network, resulting in mechanical reinforcement of the hydrogel. Another strategy for making biomimetic mineralized hydrogels is to use polymers modified with metal-binding ligands to combine with metals or metal oxides to form hydrogels through a metal coordination mineralization-induced cross-linking strategy. Based on these two methods, various biomimetic mineralized hydrogels have been studied for a variety of properties for biomedical applications.

[0006] However, the current preparation methods of mineralized hydrogels are mainly based on reaction-diffusion mechanisms, which take a long time to prepare, lack adaptive integration, and usually require additional chemical crosslinkers to resist damage to the hydrogel network caused by long-term immersion. The preparation is complex and not conducive to clinical transformation. There have been no reports on the preparation of biomimetic mineralized hydrogels with multi-factor sequential release by highly mimicking the natural dynamic biomineralization process. Summary of the invention

[0007] In view of this, the technical problem to be solved by the present invention is to provide a multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capability and a preparation method and application thereof. The biomimetic mineralized hydrogel provided by the present invention has multi-factor sequential release capability and has excellent biocompatibility and biodegradability.

[0008] The present invention provides a biomimetic mineralized hydrogel, which is obtained from negatively charged degradable polymer compounds, phosphate-containing small molecules, metal ions and bioactive factors;

[0009] The phosphate-containing small molecule has one or more structures shown in Formula 2-1 to Formula 2-5;

[0010]

[0011]

[0012] In certain embodiments of the present invention, the phosphate-containing small molecule is selected from one or more compounds having structures of Formula 2-a to Formula 2-f;

[0013]

[0014] The biomimetic mineralized hydrogel provided by the present invention is a biomimetic mineralized hydrogel with multi-factor sequential release capability. Negatively charged degradable polymer compounds and phosphate-containing small molecules are mixed in a solvent to form a precursor hydrogel under alkaline conditions, and then the precursor hydrogel, metal ions and bioactive factors are prepared by in situ mineralization and cross-linking.

[0015] The phosphate-containing small molecule described in the present invention is a functional small molecule loaded in the biomimetic mineralized hydrogel, which gives the entire system certain functionality while achieving mineralization. Since the phosphate-containing small molecule combines with the metal ions to form dense crystals, long-term and effective release is achieved. At the same time, the physical interaction strength between the metal ions and the bioactive factors in the biomimetic mineralized hydrogel is different, thereby achieving a difference in release rate. In addition, the presence of bioactive factors also gives the gel biological functions such as tumor inhibition, angiogenesis promotion, antibacterial and skin wound repair. The metal ions described in the present invention are selected from Ca 2+ Mg 2+ 、Zn 2+ , Cu 2+ , Fe 3+ , Sr 2+ and Mn 2+ The bioactive factor of the present invention is selected from one or more of small molecule drugs, growth factors and cells, preferably selected from one or more of bone morphogenetic protein (BMP-2), platelet-derived growth factor-BB (PDGF-BB), vascular endothelial growth factor (VEGF), doxorubicin (DOX), paclitaxel (PTX), platinum drugs and bone marrow mesenchymal stem cells (BMSCs).

[0016] The negatively charged degradable polymer compound of the present invention provides a three-dimensional network structure and a mineralization template for the entire bone repair material. Specifically, the negatively charged degradable polymer compound is a negatively charged carboxylate-containing degradable polymer compound. More specifically, the negatively charged degradable polymer compound has one or more of the structures shown in Formula 1-1 to Formula 1-5:

[0017]

[0018]

[0019] Wherein, R is H or CH 2 COO -;

[0020] The n, m, x, y and b are all degrees of polymerization, 30≤n≤7000, 50≤m≤8500, 20≤x≤6500, 100≤y≤6000, 20≤b≤6500.

[0021] Preferably, the negatively charged degradable polymer compound is selected from one or more of polyamino acids, polypeptides, proteins, sodium alginate, sodium carboxymethyl cellulose, carboxymethyl chitosan and sodium hyaluronate, and the protein includes one or more of gelatin, collagen, albumin, bovine serum albumin and silk fibroin.

[0022] In some embodiments of the present invention, the negatively charged degradable polymer compound is gelatin. Preferably, the gelatin has a gel strength of 50 g Bloom to 500 g Bloom, more preferably 100 g Bloom to 300 g Bloom.

[0023] In some embodiments of the present invention, the negatively charged degradable polymer compound is collagen. Preferably, the relative molecular mass of the collagen is 10 kDa to 1650 kDa, more preferably 100 kDa to 300 kDa.

[0024] In some embodiments of the present invention, the negatively charged degradable polymer compound is silk fibroin. Preferably, the molecular weight of the silk fibroin is 100 kDa to 1650 kDa, more preferably 100 kDa to 300 kDa.

[0025] In some embodiments of the present invention, the negatively charged degradable polymer compound is sodium carboxymethyl cellulose. Preferably, the viscosity of the sodium carboxymethyl cellulose is in the range of η=500mPa·s to 15000mPa·s, more preferably 500mPa·s to 5000mPa·s.

[0026] In some specific embodiments of the present invention, the negatively charged degradable polymer compound is sodium alginate. Preferably, the molecular weight of the selected sodium alginate is 11 kDa to 1850 kDa, more preferably 100 kDa to 400 kDa.

[0027] In some specific embodiments of the present invention, the negatively charged degradable polymer compound is carboxymethyl chitosan. Preferably, the viscosity of the carboxymethyl chitosan is in the range of η=10mPa·s to 100mPa·s, more preferably 40mPa·s to 80mPa·s.

[0028] In some specific embodiments of the present invention, the negatively charged degradable polymer compound is sodium hyaluronate. Preferably, the molecular weight of the sodium hyaluronate is 8.2 kDa to 2460 kDa, more preferably 800 kDa to 1000 kDa.

[0029] The method for preparing the biomimetic mineralized hydrogel of the present invention comprises the following steps:

[0030] Under alkaline conditions, phosphate-containing small molecules, negatively charged degradable polymer compounds, metal ion compounds and bioactive factors are mixed in a solvent to obtain a prefabricated hydrogel; the obtained prefabricated hydrogel is allowed to stand to obtain a biomimetic mineralized hydrogel.

[0031] The phosphate-containing small molecules, negatively charged degradable polymer compounds and bioactive factors of the present invention are the same as those described above and will not be described in detail. The metal ion compound of the present invention is selected from one or more of calcium chloride, magnesium chloride, zinc chloride, ferric chloride, strontium chloride, manganese chloride, calcium acetate, magnesium acetate, zinc acetate, ferric acetate, strontium acetate and manganese acetate. The solvent of the present invention is selected from one or more of water, saline, phosphate buffer, borate buffer, etc. The mass concentration of the phosphate-containing small molecules of the present invention in the solvent is 0.01% to 12%, preferably 4%. The mass concentration of the negatively charged degradable polymer compound of the present invention in the solvent is 0.1% to 55%, preferably 15%. The mass concentration of the metal ion compound of the present invention in the solvent is 0.1% to 5%, preferably 0.8%; the mass concentration of the bioactive factor in the solvent is 0.01% to 5%, more preferably 0.5%.

[0032] The pH value of the alkaline conditions described in the present invention is 9 to 10. The alkaline conditions described in the present invention are provided by alkaline substances, and the alkaline substances are selected from one or more of NaOH, KOH, sodium carbonate, sodium bicarbonate and triethylamine. The molar ratio of the phosphate group of the phosphate-containing small molecule described in the present invention to the alkaline group of the alkaline substance in the system is (0.01 to 100):1, preferably (0.01 to 20):1; the molar ratio of the carboxylate group of the negatively charged degradable polymer compound to the phosphate group of the phosphate-containing small molecule is (0.01 to 100):1, preferably (0.01 to 20):1.

[0033] The temperature of the blending of the present invention is 0°C to 65°C, and the time of the blending is 5min to 20min. The blending of the present invention can be carried out by mechanical stirring, manual stirring and the like. The temperature of the standing temperature of the present invention is 0°C to 80°C, preferably 0°C to 65°C, more preferably 0°C to 60°C, and more preferably 25°C to 40°C. The standing time is 0.5h to 36d, preferably 0.5h to 25d, more preferably 0.5h to 21d, and more preferably 0.5h to 2d. The prefabricated hydrogel of the present invention is gelled by physical interaction. Specifically, during the process of standing the obtained prefabricated hydrogel, the prefabricated hydrogel will undergo in-situ mineralization and cross-linking, and finally obtain a biomimetic mineralized hydrogel. The water content of the biomimetic mineralized hydrogel obtained by the present invention is preferably 50% to 99%. The prefabricated hydrogel of the present invention is the initial state of the biomimetic mineralized hydrogel, which exhibits liquid or typical soft material characteristics at the beginning of standing. As the standing temperature increases and the standing time increases, the crystallization rate accelerates, the crystallinity inside the gel gradually increases, and the crystal structure becomes more perfect, thereby in situ enhancing the mechanical properties of the obtained biomimetic mineralized hydrogel by mineralizing to form nanoparticles in the polymer matrix.

[0034] In certain embodiments of the present invention, the method for preparing the biomimetic mineralized hydrogel of the present invention comprises the following steps:

[0035] A) under alkaline conditions, mixing a phosphate-containing small molecule and a negatively charged degradable polymer compound in a solvent to obtain a precursor hydrogel;

[0036] B) blending the metal ion compound, the bioactive factor and the precursor hydrogel obtained in step A) to obtain a prefabricated hydrogel;

[0037] C) allowing the prefabricated hydrogel obtained in step B) to stand to obtain a biomimetic mineralized hydrogel.

[0038] In step A) of the present invention, first, under alkaline conditions, a phosphate-containing small molecule and a negatively charged degradable polymer compound are blended in a solvent to obtain a precursor hydrogel. Specifically, the present invention blends a phosphate-containing small molecule, a negatively charged degradable polymer compound and an alkaline substance in a solvent to obtain a precursor hydrogel. More specifically, the present invention dissolves the phosphate-containing small molecule in an alkaline substance solution to obtain a first intermediate, and blends the negatively charged degradable polymer compound with the obtained first intermediate to obtain a precursor hydrogel. The blending temperature of step A) of the present invention is 0°C to 65°C, preferably 4°C to 65°C, and more preferably 25°C to 40°C; the blending time of step A) is 5min to 20min, preferably 10min. Preferably, the water content of the precursor hydrogel obtained by the present invention is 50% to 99%.

[0039] After the precursor hydrogel is obtained in step A), the present invention blends the metal ion compound, the bioactive factor and the obtained precursor hydrogel in step B) to obtain a prefabricated hydrogel. Specifically, step B) blends the mixed solution of the metal ion compound and the bioactive factor with the precursor hydrogel obtained in step A) to obtain a prefabricated hydrogel. More specifically, step B) blends the metal ion compound and the bioactive factor in a solvent to obtain a second intermediate, and slowly drops the obtained second intermediate into the precursor hydrogel obtained in step A) under stirring to obtain a prefabricated hydrogel. The blending temperature of step B) of the present invention is 10°C to 65°C, and the blending time of step B) is 5min to 20min.

[0040] After the prefabricated hydrogel is obtained in step B) of the present invention, step C) the prefabricated hydrogel is allowed to stand to obtain a biomimetic mineralized hydrogel. The standing is the same as the above and will not be described in detail.

[0041] The preparation method of the biomimetic mineralized hydrogel provided by the present invention prepares the hydrogel by a "one-pot" blending method, which has a simple process, easy raw materials, low cost, and is easy to achieve large-scale preparation, and has great potential for clinical transformation. The present invention uses a negatively charged degradable polymer compound as a mineralization template, and the phosphate-containing small molecule itself crystallizes and acts as a nucleation site to cause metal ion deposition mineralization and crystal nucleus growth. In addition, the negative charge of the mineralization template can slow down the crystallization rate of the crystal, thereby forming a more compact crystal, and finally the negatively charged groups in the mineralization template, the phosphates in the phosphate-containing small molecules, the metal ions and the co-coordination of the bioactive factors and the crystallization of the system form a hydrogel cross-linked with mineralized crystals. The hydrogel preparation process constructed by this method is simple, and the prefabricated hydrogel in the initial state can be injectable and automatically adapt to irregular bone wounds. The gel after in situ mineralization can provide mechanical support for the wound as a porous scaffold, and releases the loaded bioactive factors in order as needed to efficiently promote bone tissue repair, which is expected to be applied to clinical bone repair.

[0042] After obtaining the biomimetic mineralized hydrogel according to the preparation method of the biomimetic mineralized hydrogel provided by the present invention, the obtained biomimetic mineralized hydrogel is placed in a phosphate-containing environment and soaked to perform ion replacement to obtain a biomimetic phosphate hydrogel. Specifically, the above-mentioned biomimetic mineralized hydrogel is placed in a phosphate-containing environment and allowed to stand, and soaked to perform sufficient ion replacement until equilibrium is achieved to obtain a biomimetic phosphate hydrogel. The phosphate-containing environment of the present invention includes a human body fluid environment or a simulated human body fluid environment, including but not limited to one or more of a buffer solution containing phosphate, bones, body fluids, etc. The temperature of the ion replacement of the present invention is 4°C to 40°C, and the time of the ion replacement is 20d to 25d.

[0043] The present invention also provides the use of the biomimetic mineralized hydrogel described in any of the above technical solutions and the biomimetic mineralized hydrogel obtained by the preparation method described in any of the above technical solutions in the preparation of bone repair materials. Specifically, the biomimetic mineralized hydrogel described in the present invention has high adhesion properties and can be coated on a substrate and applied to human tissue as a bone repair material or directly act on human tissue as a bone repair material, and the human tissue includes but is not limited to skin wounds, bone wounds, human organs, etc.

[0044] If the biomimetic mineralized hydrogel of the present invention is coated on a substrate and used in human tissue as a bone repair material, the substrate includes but is not limited to one or more of a neutral glass sheet, a positively charged glass sheet, a negatively charged glass sheet, polyethylene, polycarbonate, polypropylene, polytetrafluoroethylene, polymethyl methacrylate, a metal substrate, wood, silicone, rubber, latex, etc.

[0045] If the biomimetic mineralized hydrogel of the present invention is directly applied to human tissue as a bone repair material, the biomimetic mineralized hydrogel of the present invention can be injected and automatically adapt to irregular bone wounds in its initial state (prefabricated hydrogel). Based on its biomineralization function, it can be mineralized in situ to obtain a biomimetic mineralized hydrogel, which can then be used as a porous scaffold to provide mechanical support for the wound. The bioactive factors loaded can be released in sequence on demand to efficiently promote bone tissue repair, and it can eventually become a biological bone-like structure in an environment simulating body fluids. This indicates that after the prefabricated hydrogel is solidified into a biomimetic mineralized hydrogel in the human body, it can slowly become a biological bone-like structure through body fluid replacement and eventually degrade into a biomimetic phosphate hydrogel, and has excellent biocompatibility.

[0046] The present invention provides a multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capability, and a preparation method and application thereof. The biomimetic mineralized hydrogel provided by the present invention has good injectability, self-healing and adhesion, can automatically adapt to filling irregular bone wounds, and the mechanical properties of the gel are significantly improved by the extension of the ambient temperature of the human body or the mineralization time. In addition, the functional phosphate-containing small molecules loaded in the hydrogel can be released for a long time and effectively because they are combined with metal ions to form dense crystals, which greatly improves the drug utilization rate and reduces the drug toxicity. In addition, the intensity of the physical interaction between the metal ions and the bioactive factors loaded in the gel in the mineralized gel is different, thereby achieving a difference in the release rate, allowing specific factors to be released at a specific period of bone repair, and finally achieving sequential release on demand. As a bone repair material, it has a good ability to promote angiogenesis and bone regeneration, which is conducive to improving the efficiency of bone tissue repair. At the same time, the biomimetic mineralized hydrogel provided by the present invention can also be transformed into a biosimulated phosphate hydrogel in the later stage of bone repair. In the later stage of repair, the phosphate in the human body will replace the drug inside the hydrogel, and the phosphate will combine with the metal ions inside the hydrogel, so that the hydrogel is transformed into a hydrogel containing phosphate, and its structure is similar to the human bone component, which further promotes the repair of the bone wound surface, indicating that the biomimetic mineralized hydrogel of the present invention has good biocompatibility and biodegradability, low hemolysis rate and cytotoxicity, and the presence of bioactive factors also gives the gel tumor inhibition, promotes angiogenesis, antibacterial and skin wound repair and other biological functions, and can effectively promote bone tissue repair. From this point of view, the in situ mineralized hydrogel perfectly solves the three major shortcomings of the current bone repair materials: low biological activity, inability to release on demand, and poor adaptive integration ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 A schematic diagram of the technical route for constructing the multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capability provided by the present invention;

[0048] Figure 2 This is the surface morphology of the hydrogel in the initial state of Example 1;

[0049] Figure 3 This is the gel morphology picture of the hydrogel after curing in Example 1;

[0050] Figure 4 This is a graph showing the angular velocity-modulus test results of the hydrogel in the initial state of Example 6;

[0051] Figure 5 This is a graph showing the angular velocity-modulus test results of the hydrogel after curing in Example 6;

[0052] Figure 6 Schematic diagram of the adhesion test of hydrogel by glass plate adhesion using a tensile testing machine;

[0053] Figure 7 This is a graph showing the test results of the hydrogel adhesion performance of Example 8;

[0054] Figure 8 This is a picture of the internal morphology of the hydrogel of Example 16 after being immersed in PBS for 35 days;

[0055] Fig. 9 This is the XRD pattern of the hydrogel after curing in Example 16;

[0056] Fig.10 This is the XRD pattern of the hydrogel of Example 16 after being immersed in PBS for 35 days;

[0057] Fig.11 is the XRD pattern of the control group without adding calcium chloride solution;

[0058] Fig.12 This is a graph showing the hemolysis rate of the hydrogel of Example 16;

[0059] Fig.13 This is a morphology of red blood cells after the hydrogel of Example 16 was co-incubated with rabbit red blood cells for 3 hours;

[0060] Fig.14 This is a graph showing the cytotoxicity results of the hydrogel of Example 16;

[0061] Fig.15 This is a tube-forming image of the hydrogel of Example 16;

[0062] Fig.16 This is the μ-CT scan image of the hydrogel-treated group in Example 16. DETAILED DESCRIPTION

[0063] The present invention discloses a multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capability, and a preparation method and application thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0064] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0065] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials that meet the purity standards related to the preparation of bone tissue repair materials.

[0066] The sources and abbreviations of all raw materials in the present invention are conventional sources and abbreviations in the field, and are clear and definite in the field of their relevant uses. Those skilled in the art can purchase them from commercial sources or prepare them by conventional methods based on the abbreviations and corresponding uses.

[0067] like Figure 1 As shown, Figure 1 A schematic diagram of the technical route for constructing the multifunctional biomimetic mineralized hydrogel with multi-factor sequential release capability provided by the present invention.

[0068] The present invention will be further described below in conjunction with embodiments:

[0069] Example 1

[0070] a. Add 32.5 mg of pamidronate disodium to 1 mL of sodium hydroxide solution at pH = 9.5 at room temperature and fully dissolve to prepare a solution;

[0071] b. Add 150 mg of sodium hyaluronate (Mn = 1000 kDa) to the final solution obtained in step a and stir for 15 min to fully dissolve it to prepare a precursor hydrogel;

[0072] c. 100 mg / mL calcium chloride solution, 300 mg / mL magnesium chloride solution. Add 25 μL of calcium chloride solution and 10 μL of magnesium chloride solution to the system obtained in step b, and stir for 10 minutes to mix evenly.

[0073] d. The system obtained in step c was placed in an oven at 40°C for 24 hours to successfully prepare the hydrogel.

[0074] e. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at room temperature for 15 days to allow sufficient internal and external ion exchange to prepare a biosimulated calcium magnesium phosphate hydrogel.

[0075] Example 2

[0076] a. Add 18 mg of adenosine triphosphate to 2 mL of sodium carbonate-sodium bicarbonate buffer solution (pH = 9.4) and fully dissolve to prepare a solution;

[0077] b. Add 300 mg of gelatin (gel strength 300 g Bloom) to the final solution obtained in step a and stir for 20 min to fully dissolve it to prepare a precursor hydrogel.

[0078] Example 3

[0079] a. Prepare 350 mg / mL of magnesium chloride solution and 10 mg / mL of DOX solution, add 24 μL of magnesium chloride solution and 50 μL of DOX solution to the system obtained in Example 2, and stir well to mix;

[0080] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 60 degrees Celsius for 0.5 days.

[0081] c. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at room temperature for 15 days to allow sufficient internal and external ion exchange to prepare a biomimetic magnesium phosphate hydrogel.

[0082] Example 4

[0083] a. Prepare 350 mg / mL zinc chloride solution, 10 μg / μL BMP-2 solution, add 68 μL zinc chloride solution and 3 μL BMP-2 solution to the system obtained in Example 2, and stir well to mix;

[0084] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 24 degrees Celsius for 3 days.

[0085] c. After the final solidification, the hydrogel was immersed in in vitro simulated body fluid PBS at room temperature for 15 days to allow sufficient internal and external ion exchange to prepare a biomimetic zinc phosphate hydrogel.

[0086] Example 5

[0087] a. Prepare 350 mg / mL of calcium acetate solution and 350 mg / mL of strontium chloride solution, add 24 μL of calcium acetate solution and 10 μL of strontium chloride solution to the system obtained in Example 2, and stir well to mix;

[0088] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 37 degrees Celsius for 1 day.

[0089] c. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at room temperature for 15 days to allow sufficient internal and external ion exchange to prepare a bio-mimicking calcium strontium phosphate hydrogel.

[0090] Example 6

[0091] a. Add 40 mg of pamidronate disodium to 2 mL of sodium carbonate-sodium bicarbonate buffer solution (pH = 9.4) and fully dissolve to prepare a solution;

[0092] b. Add 180 mg of sodium alginate (Mn = 300 kDa) to the final solution obtained in step a and stir for 20 min to fully dissolve it;

[0093] c. Prepare 350 mg / mL zinc chloride solution and 10 μg / μL VEGF solution, add 12 μL of zinc chloride solution and 2 μL of VEGF solution to the system obtained in step b, and stir well to mix evenly;

[0094] d. The hydrogel can be successfully prepared by placing the system obtained in step c at 15 degrees Celsius for 10 days.

[0095] e. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at room temperature for 30 days to allow sufficient internal and external ion exchange to prepare a biomimetic zinc phosphate hydrogel.

[0096] Example 7

[0097] a. Add 48 mg of adenine nucleoside diphosphate to 2 mL of PBS buffer solution (pH = 7.5), adjust the pH of the solution to about 9 using 100 mg / mL NaOH, and prepare the solution;

[0098] b. Add 200 mg of sodium carboxymethyl cellulose (η = 600 ~ 3000 mPa · s) to the final solution obtained in step a and stir for 15 minutes to fully dissolve it to prepare a precursor hydrogel.

[0099] Example 8

[0100] a. Prepare 500 mg / mL calcium chloride solution, 10 μg / μL VEGF solution and PDGF-BB solution, add 60 μL calcium chloride solution, 3 μL VEGF solution and 3 μL PDGF-BB solution to the system obtained in Example 7, and stir for 15 min to mix well;

[0101] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 25 degrees Celsius for 5 days.

[0102] c. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at 37 degrees Celsius for 15 days to allow sufficient internal and external ion exchange to prepare a biomimetic calcium phosphate hydrogel.

[0103] Example 9

[0104] a. Prepare 350 mg / mL zinc chloride solution and 10 μg / μL PDGF-BB solution, add 60 μL zinc chloride solution and 3 μL PDGF-BB solution to the system obtained in Example 7, and stir for 15 min to mix well;

[0105] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 20 degrees Celsius for 4 days.

[0106] c. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at 25 degrees Celsius for 20 days to allow sufficient internal and external ion exchange to prepare a biomimetic zinc phosphate hydrogel.

[0107] Example 10

[0108] a. Add 30 mg of cyclohexane hexaphosphate to 2 mL of sodium carbonate-sodium bicarbonate buffer solution (pH = 9.4) and fully dissolve to prepare a solution;

[0109] b. Add 500 mg of silk fibroin (Mn = 100 kDa) to the final solution obtained in step a and stir for 15 min to fully dissolve it;

[0110] c. Prepare 400 mg / mL calcium chloride solution and 10 mg / mL DOX solution, add 50 μL of calcium chloride solution and 50 μL of DOX solution to the system obtained in step b, and stir well to mix;

[0111] d. The hydrogel can be successfully prepared by placing the system obtained in step c at 37 degrees Celsius for 1 day.

[0112] e. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at room temperature for 25 days to allow sufficient internal and external ion exchange to prepare a biomimetic calcium phosphate hydrogel.

[0113] Embodiment 11

[0114] a. Add 60 mg of clindamycin phosphate to 2 mL of PBS (pH = 7.5), adjust the system pH to about 9 using 50 mg / mL NaOH solution, and prepare the solution;

[0115] b. Add 600 mg of collagen (η=30-50 mPa·s) to the final solution obtained in step a and stir for 10 min to fully dissolve it to prepare a precursor hydrogel.

[0116] Example 12

[0117] a. Add 60 mg of pamidronate disodium to 2 mL of PBS (pH = 7.5), adjust the system pH to about 9 using 100 mg / mL KOH solution, and prepare the solution;

[0118] b. Add 650 mg of silk fibroin (Mn=200 kDa) to the final solution obtained in step a and stir for 10 min to fully dissolve it to prepare a precursor hydrogel.

[0119] Embodiment 13

[0120] a. Add 50 mg of pamidronate disodium to 2 mL of PBS (pH = 7.5), adjust the system pH to about 9 using 50 mg / mL triethylamine solution, and configure the solution;

[0121] b. Add 500 mg of sodium hyaluronate (Mn=1000 kDa) to the final solution obtained in step a and stir for 10 min to fully dissolve it to prepare a precursor hydrogel.

[0122] Embodiment 14

[0123] a. Prepare 600 mg / mL calcium chloride solution and 300 mg / mL magnesium chloride solution, add 60 μL of calcium chloride solution and 15 μL of magnesium chloride solution to the system obtained in Example 11, and stir well to mix well.

[0124] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 30 degrees Celsius for 1 day.

[0125] c. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at room temperature for 20 days to allow sufficient internal and external ion exchange to prepare a biomimetic calcium magnesium phosphate hydrogel.

[0126] Embodiment 15

[0127] a. Prepare 600 mg / mL of calcium acetate solution, 10 mg / mL of DOX solution and 10 μg / μL of PDGF-BB solution, add 60 μL of calcium acetate solution, 40 μL of DOX solution and 5 μL of PDGF-BB solution to the system obtained in Example 12, and stir well to mix;

[0128] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 40 degrees Celsius for 1 day.

[0129] c. After the final solidification, the hydrogel was immersed in an in vitro simulated body fluid PBS at room temperature for 20 days to allow sufficient ion exchange inside and outside to prepare a biomimetic calcium phosphate hydrogel.

[0130] Example 16

[0131] a. Prepare 500 mg / mL calcium chloride solution, 400 mg / mL magnesium chloride solution and 10 μg / μL PDGF-BB solution, add 66 μL calcium chloride solution, 10 μL magnesium chloride solution and 4 μL PDGF-BB solution to the system obtained in Example 13, and stir well to mix;

[0132] b. The hydrogel can be successfully prepared by placing the system obtained in step a at 37 degrees Celsius for 1 day.

[0133] c. After the final solidification, the hydrogel was immersed in in vitro simulated body fluid PBS at room temperature for 15 days to allow sufficient internal and external ion exchange to prepare a biomimetic zinc phosphate hydrogel.

[0134] Embodiment 17

[0135] The surface morphology of the hydrogel in its initial state and after being cured at the same temperature for different periods of time was tested. Specifically, the hydrogels prepared in Examples 1, 3 to 5 in their initial state (just after stirring) and after being cured were placed in a -20°C refrigerator for 12 hours and then placed in a freeze dryer for freeze drying to remove water. The obtained freeze-dried hydrogel was placed in liquid nitrogen for rapid freezing and quickly broken, and the surface morphology of the cross section was observed by scanning electron microscopy.

[0136] Reference Figure 2 and Figure 3 , Figure 2 This is the surface morphology of the hydrogel in the initial state of Example 1, where the internal grid of the gel is irregular small holes. Figure 3 This is the gel morphology of the hydrogel of Example 1 after curing. The three-dimensional skeleton becomes macroporous and has thicker network walls.

[0137] Embodiment 18

[0138] The change of hydrogel modulus was demonstrated by testing the rheological behavior of the hydrogel in its initial state and after being cured at the same temperature for different periods of time. Figure 4 and Figure 5 , Figure 4 This is a graph showing the angular velocity-modulus test results of the initial state of the hydrogel in Example 6. Figure 5 The angular velocity-modulus test result diagram of the hydrogel after curing of Example 6 is shown in FIG. Figure 4 result, Figure 5 The hydrogel has a higher elastic modulus. It proves that the initial state of the hydrogel is amorphous with a low elastic modulus, which is easy to apply. After curing, the hydrogel has a high elastic modulus and is easier to fill and fix the wound.

[0139] Embodiment 19

[0140] The adhesion performance of hydrogels was tested to prove that hydrogels can better adhere to and fix wounds. Specifically, the adhesion performance of hydrogels was tested by using a tensile testing machine to adhere to a glass plate. Figure 6 As shown, Figure 6Schematic diagram of the adhesion performance of hydrogel tested by glass plate adhesion using a tensile testing machine. Take 32 mg of gel and apply it to the edge of glass plate A, with an application area of ​​25 mm × 12.5 mm. Bridge glass plate B to the gel application area of ​​glass plate A, press the two glass plates for 1 minute, and use a tensile testing machine to test to obtain the tensile stress F. The instrument setting parameters are tension speed = 10 mm / min, maximum limit force = 50 N. Finally, the adhesion of the gel to the glass plate is obtained by the formula Adhesive strength = F / (25 mm × 25 mm).

[0141] Results reference Figure 7 , Figure 7 This is a graph showing the test results of the hydrogel adhesion performance of Example 8. The results show that the adhesion of the hydrogel to the substrate is about 50 kPa, which has good adhesion behavior and can better fix the wound surface. It is worth noting that the addition of bioactive factors has almost no effect on the adhesion of the gel in the initial state.

[0142] Embodiment 20

[0143] By testing the changes in the internal structure of the solidified hydrogel after immersion in the external environment, the change in the cross-linking structure of the gel was proved, from a drug hydrogel to a phosphate hydrogel. Specifically, 300 mg of the mineralized hydrogel was placed in 1 mL of PBS at 37 ° C, and the PBS in the test tube was taken out at different time points, and a new 1 mL of PBS was added. After the gel was replaced in PBS for 35 days, the gel was taken out and placed in a -20 ° C refrigerator for freezing, and then dried using a freeze dryer. Finally, the freeze-dried sample was obtained using a scanning electron microscope to obtain a photo of the internal morphology of the gel and made into a powder for XRD analysis of the cross-linking structure inside the gel.

[0144] Results reference Figure 8 , Figure 8 The internal morphology of the hydrogel of Example 16 after being immersed in PBS for 35 days is shown in Figure 2. Figure 3 , the gel pore size becomes smaller and the cross-linked network becomes denser, proving the change of the cross-linked structure inside the gel.

[0145] Embodiment 21

[0146] The XRD test showed that the cross-linking structure of the cured hydrogel changed from drug hydrogel to phosphate hydrogel after being immersed in the external environment. Fig. 9 and Fig.10 , Fig. 9 This is the XRD diagram of the hydrogel after curing in Example 16. Fig.10 This is the XRD pattern of the hydrogel of Example 16 after being immersed in PBS for 35 days. Fig. 9 and Fig.10Both showed strong diffraction peaks belonging to calcium phosphate crystals, so ADA and Ca 2+ The release is relatively slow. Fig.11 This is the XRD pattern of the control group without calcium chloride solution. It can be seen that Mg 2+ It does not form a crystal structure in the system, but is loosely bound in the system, so Mg 2+ The release is faster in the early stage, thus achieving sequential release on demand.

[0147] Embodiment 22

[0148] The blood compatibility of the hydrogel was evaluated by a hemolysis experiment. Specifically, 2 mL of fresh rabbit blood was first added to 20 mL of normal saline, centrifuged at 1500 rpm / min for 10 minutes in a centrifuge, the upper supernatant was discarded, and 20 mL of normal saline was newly added to the blood cells in the lower layer, and the centrifugation was repeated 3 times. Collect the lower layer of blood cells. The lower layer of blood cells was configured into a 2% blood cell suspension and co-cultured with the hydrogel at 37°C. The negative control group was pure normal saline, and the positive control group was 1% tritonX-100. After 3 hours, the supernatant was taken out, and the absorbance at 545 nm was tested using a UV spectrophotometer, and the hemolysis rate was finally obtained by the following formula.

[0149] Hemolysis rate % = (Abs gel group - Abs negative group) / (Abs positive group - Abs negative group) × 100%;

[0150] Results reference Fig.12 , Fig.12 This is a graph showing the hemolysis rate of the hydrogel of Example 16. The hemolysis rate is less than 5%, which proves that the hydrogel has excellent blood compatibility.

[0151] Embodiment 23

[0152] Most of the supernatant of the centrifuged blood cells was removed, leaving about 50 μL of supernatant to blow away the cells, then 10 μL of liquid was aspirated and dropped on a glass slide, and finally the glass slide was placed under a fluorescent inverted microscope for observation and photography.

[0153] Results reference Fig.13 , Fig.13 This is the morphology of the red blood cells after the hydrogel of Example 16 was co-incubated with rabbit red blood cells for 3 hours. The red blood cells in the field of view showed a biconcave disc-shaped structure, indicating that the gel has good blood compatibility.

[0154] Embodiment 24

[0155] The biocompatibility of the hydrogels was evaluated by cytotoxicity experiments.

[0156] First, bone mesenchymal stem cells (BMSCs) were cultured. 8000 cells were seeded in each well of a 96-well plate and incubated at 37°C with 5% CO2 After culturing for 24 h in cell culture medium, the original culture medium was discarded and the cell culture medium containing gel extract was added. The cells were then cultured at 37°C and 5% CO. 2 The cells were cultured for 24 h under the same conditions, and the negative control group was pure cell culture medium. The culture medium containing the gel extract was then discarded, and 100 μL of serum-free culture medium containing CCK8 was added to each well. The cells were cultured at 37°C and 5% CO 2 After incubation for 2 h under the same conditions, the absorption spectrum at 450 nm was measured using an ELISA reader, and the cell survival rate was finally calculated using the following formula.

[0157] Cell survival rate % = OD gel group / OD negative group × 100%;

[0158] Results reference Fig.14 , Fig.14 This is a graph showing the cytotoxicity results of the hydrogel of Example 16. The cell survival rate is close to 100%, demonstrating that the hydrogel has excellent biocompatibility.

[0159] Embodiment 25

[0160] The ability of the gel to promote angiogenesis in vitro was evaluated by a cell tube formation experiment. Specifically, human umbilical vein endothelial cells (HUVECs) were first cultured, 50 μL of matrix gel was added to each well of a 96-well plate and allowed to stand for 0.5 h, and then 100 μL of gel extract containing 8,000 cells was inoculated on the matrix gel. After incubation for 6 hours, the tube formation ability of HUVECs was observed under a fluorescence microscope. The results refer to Fig.15 , Fig.15 This is an image of the tube-forming hydrogel of Example 16. It can be seen from the image that the gel has a good ability to promote blood vessel formation.

[0161] Embodiment 26

[0162] The effect of hydrogel in promoting bone repair in vivo was evaluated using a rat skull model. Specifically, healthy adult female SD rats (6-8 weeks, 200-240g) were randomly divided into groups. Two circular defects with a diameter of 5 mm were drilled on both sides of the center of the rat skull with a drill bit. 64 mg of hydrogel was used to treat bone defects. 28 days after surgery, all rats were killed, and skull specimens were collected and immersed in a 4°C paraformaldehyde solution (4%) for 24 hours. The bone repair effect of the gel was evaluated by μ-CT scanning. The results refer to Fig.16 , Fig.16 This is the μ-CT scanning image of the hydrogel-treated group in Example 16. From the image, it can be seen that the hydrogel has a good effect in promoting bone repair.

[0163] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A biomimetic mineralized hydrogel, characterized in that: It is obtained from negatively charged degradable polymer compounds, phosphate-containing small molecules, metal ions and bioactive factors; The phosphate-containing small molecule has one or more structures shown in Formula 2-1 to Formula 2-5; 2. The biomimetic mineralized hydrogel according to claim 1, characterized in that: The metal ion is selected from Ca 2+ Mg 2+ 、Zn 2+ , Cu 2+ , Fe 3+ , Sr 2+ and Mn 2+ One or more of .

3. The biomimetic mineralized hydrogel according to claim 1, characterized in that: The bioactive factor is selected from one or more of bone morphogenetic protein, platelet-derived growth factor-BB, vascular endothelial growth factor, doxorubicin, paclitaxel, platinum drugs and bone marrow mesenchymal stem cells.

4. The biomimetic mineralized hydrogel according to claim 1, characterized in that: The negatively charged degradable polymer compound has one or more structures shown in Formula 1-1 to Formula 1-5: Wherein, R is H or CH2COO - ; The n, m, x, y and b are all degrees of polymerization, 30≤n≤7000, 50≤m≤8500, 20≤x≤6500, 100≤y≤6000, 20≤b≤6500.

5. The biomimetic mineralized hydrogel according to claim 1, characterized in that: The negatively charged degradable polymer compound is selected from one or more of polyamino acids, polypeptides, proteins, sodium alginate, sodium carboxymethyl cellulose, carboxymethyl chitosan and sodium hyaluronate.

6. The method for preparing the biomimetic mineralized hydrogel according to any one of claims 1 to 5, characterized in that: The following steps are involved: Under alkaline conditions, phosphate-containing small molecules, negatively charged degradable polymer compounds, metal ion compounds and bioactive factors are mixed in a solvent to obtain a prefabricated hydrogel; the obtained prefabricated hydrogel is allowed to stand to obtain a biomimetic mineralized hydrogel.

7. The method for preparing the biomimetic mineralized hydrogel according to claim 6, characterized in that: The mass of the negatively charged degradable polymer compound in the solvent is 0.1% to 55%; The mass concentration of the phosphate-containing small molecule in the solvent is 0.01% to 12%; The mass concentration of the metal ion compound in the solvent is 0.1% to 5%; The mass of the bioactive factor in the solvent is 0.01% to 5%.

8. The method for preparing the biomimetic mineralized hydrogel according to claim 6, characterized in that: The standing temperature is 0°C to 80°C, and the standing time is 0.5h to 36d.

9. The method for preparing the biomimetic mineralized hydrogel according to any one of claims 6 to 8, characterized in that: The obtained biomimetic mineralized hydrogel is placed in a phosphate-containing environment and immersed therein to perform ion replacement to obtain a biomimetic phosphate hydrogel.

10. Use of the biomimetic mineralized hydrogel according to any one of claims 1 to 5 and the biomimetic mineralized hydrogel obtained by the preparation method according to any one of claims 6 to 9 in the preparation of bone repair materials.